The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jcpp.12477
|View full text |Cite
|
Sign up to set email alerts
|

Positive parenting and children's prosocial behavior in eight countries

Abstract: Background Research supports the beneficial role of prosocial behaviors on children’s adjustment and successful youth development. Empirical studies point to reciprocal relations between negative parenting and children’s maladjustment, but reciprocal relations between positive parenting and children’s prosocial behavior are understudied. In the present study reciprocal relations between two different dimensions of positive parenting (quality of the mother-child relationship and the use of balanced positive dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
94
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 55 publications
15
94
0
6
Order By: Relevance
“…The longitudinal findings support the conclusion that mothers served as socializing agents of children's trust beliefs in physicians and children served as socializing agents of their mothers' trust beliefs in physicians. These findings are consistent with the proposed the effects of reciprocity between mothers and children on the children's psychosocial development (Pastorelli et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The longitudinal findings support the conclusion that mothers served as socializing agents of children's trust beliefs in physicians and children served as socializing agents of their mothers' trust beliefs in physicians. These findings are consistent with the proposed the effects of reciprocity between mothers and children on the children's psychosocial development (Pastorelli et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Apparently, children who are more sympathetic receive more warmth and support from parents and teachers. This finding supports the view that children shape the way in which adults behave towards them (Barnett et al, ; Pastorelli et al, ). Yet, bidirectional relations could not be confirmed, as adult responsiveness did not account for the change in sympathy from 5 to 6 and from 6 to 7 years.…”
Section: Discussionsupporting
confidence: 87%
“…The results of the study showed that mothers who engaged in these positive parenting behaviors were more likely to use supportive emotion socialization practices. The link between positive parenting and prosocial behaviors has been supported strongly in previous studies (e.g., Chan, ; Pastorelli et al, ; Zhou et al, ). However, to the best of our knowledge, the mediating role of supportive emotion socialization practices within this relation has not been examined before.…”
Section: Discussionsupporting
confidence: 58%